The Evolutionary History and Functional Divergence of Trehalase (treh) Genes in Insects - Nardelli, Andrea; Vecchi, Matteo; Mandrioli, Mauro; Manicardi, Gian Carlo (Frontiers in Physiology, 2019)
Trehalases (treh) have been found in different organisms, such as bacteria, fungi, yeast, nematodes, insects, vertebrates and plants. Their biochemical properties are extremely variable and not yet fully understood. Gene expression patterns have shown differences among insect species suggesting a potential functional diversification of trehalase enzymes during their evolution. A second gene family encoding for enzymes with hypothetical trehalase activity has bene been repeatedly annotated in insect genome as acid trehalases/acid trehalase-like (ath), but its functional role is still not clear. The currently available large amount of genomic data from many insect species may enable deeper studies allowing a better understanding of the evolutionary history, the phylogenetic relationships and possible roles of trehalase encoding genes in this taxon. The aim of the present study is to infer the evolutionary history of trehalases and acid trehalase genes in insects and analyse the trehalase functional divergence during their evolution, combining nucleotides sequences phylogenyphylogenetic, protein conservation and genomic synteny/colinearity analyses.